Effect of TNF-Gold Nanoparticles Combination on Kidney and Liver Parameters of Female Mice (Iraqi Journal of Medical Sciences, 2022)
Background: Nanomedicine has emerged as a powerful platform for applying nanotechnology in the prevention and treating many diseases.Objective: To investigate the toxicity of designated anti-cancer drugs composed of gold nanoparticles (GNPs), tumor necrosis factor-alpha (TNF-?), and cysteine-Alanine-Leucine-Asparagine-Asparagine (CALNN) peptide on kidney and liver parameters, using animals’ model.Methods: A Combination of TNF-? and CALNN peptide on the surface of GNPs were achieved depending on formation of dative covalent bond between molecules and pH of solutions, which leads to react with active groups of different molecules of nanoparticles, which characterized using ultraviolet visible spectroscopy. Moreover, their effects on kidney and liver blood variables had been examined. These blood values included measurement of the glutamic oxaloacetic transaminase, glutamic pyruvic transaminase and alkaline phosphatase, creatinine, and urea levels after intraperitoneal injection of an anti-cancer drug in female albino mice.Results: Overall, the results indicated that there was no significant change in the concentration of different biochemical values between treated and control groups.Conclusion: The results suggest that GNPs-TNF-?-CALNN combination have no harmful impact on kidney and liver organs of tested mice.Keywords: Nanomedicine, GNPs, TNF-?, CALNN peptide, drug delivery, cytotoxicity Citation: Abood NA, Kadhim HS, Jabir MS. Effect of TNF-gold nanoparticles combination on kidney and liver parameters of female mice. Iraqi JMS. 2022; 20(2): 245-251. doi: 10.22578/IJMS.20.2.12